2018
DOI: 10.1016/j.jcou.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrocatalytic performance of nanostructured p-n junction NtTiO2/NsCuO electrode in the selective conversion of CO2 to methanol at low bias potentials

Abstract: Aiming a selective reduction of CO 2 to methanol, a p-n junction semiconductor was constructed based on CuO nanospheres (NsCuO) deposited at TiO 2 nanotubes (NtTiO 2). The NtTiO 2 /NsCuO material demonstrated smaller charge transfer resistance, smaller flat band potential and wider optical absorption when compared with NtTiO 2 and/or Ti/TiO 2 nanoparticles coated by higher size particles of CuO (Ti/TiO 2 /CuO). The selective reduction of dissolved CO 2 to methanol was promoted at lower potential of +0.2 V and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…[139] In the Z-scheme and the Type II charge transfer process, the photo-induced charges will be spatially separated in the semiconductors. [15,140] Especially in the Type II scheme, the spatial separation improves the energy conversion efficiency of the photocatalysts due to the decreased opportunities for charge recombination. [139] All of those processes are related to p-n junctions.…”
Section: Heterojunction Of Different 2d Photoelectrodesmentioning
confidence: 99%
“…[139] In the Z-scheme and the Type II charge transfer process, the photo-induced charges will be spatially separated in the semiconductors. [15,140] Especially in the Type II scheme, the spatial separation improves the energy conversion efficiency of the photocatalysts due to the decreased opportunities for charge recombination. [139] All of those processes are related to p-n junctions.…”
Section: Heterojunction Of Different 2d Photoelectrodesmentioning
confidence: 99%
“…Besides, in the photoelectrocatalytic CO 2 reduction system, CO and formic acid production are relatively common, and the generation of methanol is somewhat challenging 52 . The main reason could be the generation of a CO or a formic acid from CO 2 requires two electrons, while the formation of a methanol molecule requires six electrons 47,53,58 . Therefore, adjusting the intrinsic activity of the photoelectrocatalyst to increase the yield of methanol is still a challenge.…”
Section: Light‐driven Co2 Conversion Toward Methanolmentioning
confidence: 99%
“…However, extra energy is required for the transformation of CO 2 because it is a stable molecule (∆G = −400 kJ mol −1 ) value [7]. Therefore, CO 2 conversion via photocatalytic reactions, which are involved in the utilization of solar energy, is an eco-friendly attractive route [8][9][10][11][12]. Previous studies [13][14][15][16] revealed that photocatalysts consisting of metal oxides are shown to be active in the UV-light region.…”
Section: Introductionmentioning
confidence: 99%